Knowledge Regarding Evidence-Based Guidelines on Ventilator-Associated Pneumonia Prevention Bundle among Critical Care Nurses - Pokhrel, Khushi; Dhami, Kabita; Shah, Nisha Kumari; K.C., Nyamika; K.C., Mamta; Shah, Pammi (Journal of Nobel Medical College, 2023)
Background: In critical care units, ventilator-associated pneumonia is still a frequent and possibly fatal consequence of ventilator therapy. Choosing the most urgent care and knowing how to prevent ventilator-associated pneumonia may help nurses become more alert, which will improve the quality of care and prevent a serious problem in Nepal. Thus, this study aimed to assess the knowledge regarding evidence-based guidelines on ventilator-associated pneumonia prevention bundle among critical care nurses. Materials and Methods: Data were collected through a self-administered structured questionnaire using the non-probability total enumerative sampling technique among 132 critical care nurses. Data analysis was carried out using SPSS version 20. For descriptive statistics frequency, percentage, mean, and standard deviation were calculated. For inferential statistics, the Chi-square test was used to find out the association between the levels of knowledge regarding Evidence-Based Guidelines on the VAP Prevention Bundle among Critical Care Nurses. Results: One hundred and thirty-two critical nurses participated in this study. 51.5 % had a poor level of knowledge, whereas, 45.5 % had an average level of knowledge and only 3.0 % had a good level of knowledge. There was a statistically significant association between the level of knowledge and the respondents’ working experience. Conclusion: According to the study’s findings, the majority of respondents had inadequate knowledge. Regular formal training and interactive educational sessions are required to evaluate knowledge of the VAP prevention bundle, particularly in light of the high nurse turnover rate.